(untitled) (REMUNOM, 2025)
Arterial hypertension remains one of the most prevalent chronic conditions in Brazil, strongly associated with severe cardiovascular outcomes. Within this context, pharmacists play a strategic role in Primary Health Care by supporting therapeutic adherence and improving clinical management. This study aimed to evaluate the impact of pharmaceutical follow-up on treatment adherence and hypertension control within the Brazilian Unified Health System (SUS). The methodology included a literature review in SciELO, LILACS, and PubMed, as well as the analysis of secondary data from DATASUS (2018–2023). Eligible studies addressed pharmaceutical care, therapeutic follow-up, rational medication use, and hypertension management. Results showed a progressive increase in the number of hypertensive patients monitored by pharmacists, accompanied by a reduction in complications related to the disease. Evidence indicates that structured pharmaceutical interventions allow the identification of drug-related problems, optimization of therapeutic regimens, health education, and reinforcement of self-care. Studies also demonstrated improvements in blood pressure control, decreased treatment discontinuation, and greater patient understanding of their therapy. However, challenges such as unequal distribution of professionals, structural limitations, and insufficient implementation of clinical services persist in many regions. The discussion revealed alignment between DATASUS data and literature findings, confirming the positive impact of pharmaceutical monitoring on clinical outcomes. Experiences with digital health tools showed potential as complementary strategies, although their effectiveness depends on sociocultural adaptation and users’ health literacy. In conclusion, pharmaceutical follow-up is essential for improving hypertension management and should be strengthened through public policies that expand clinical services, support continuous education, and promote multidisciplinary integration.